Comparison of adrenalectomy with conservative treatment on mild autonomous cortisol secretion: a systematic review and meta-analysis - Khadembashiri, Mohamad Mehdi; Mohseni, Shahrzad; Harandi, Hamid; Pejman Sani, Mahnaz; Khadembashiri, Mohamad Amin; Atlasi, Rasha; SeyedAlinaghi, SeyedAhmad; Mohajeri- Tehrani, Mohammadreza; Larijani, Bagher (Frontiers in Endocrinology, 2024)
Objective: This systematic review and meta-analysis was conducted to compare the benefits of adrenalectomy and conservative treatment for comorbidities associated with mild autonomous cortisol secretion (MACS) in patients diagnosed with MACS.Background: MACS is the most common benign hormone-secreting functional adrenal incidentaloma. Overproduction of cortisol is observed in MACS patients, resulting in a variety of long-term health issues, including arterial hypertension (HTN), diabetes mellitus (DM), dyslipidemia, obesity, and osteoporosis; however, the classic clinical manifestations of Cushing's syndrome (CS) are not present.Methods: A systematic search was conducted using MEDLINE, Embase, Web of Sciences, and Scopus databases on December, 2023. Two reviewers independently extracted data and assessed the quality of the included articles. A meta-analysis was performed to compare the beneficial effects of adrenalectomy versus conservative management for MACS-related comorbidities.Results: Fifteen articles were included in this study, which evaluated 933 MACS patients (384 Adrenalectomy and 501 Conservative treatment, and 48 excluded due to incomplete follow-up duration). MACS diagnosis criteria were different among the included articles. All studies, however, stated that there must be no overt CS symptoms. Meta-analysis demonstrates the overall advantage of adrenalectomy over conservative treatment for MACS-related comorbidities (Cohen's d = -0.49, 95% CI [-0.64, -0.34], p = 0.00). Subgroup analysis indicated that the systolic blood pressure (pooled effect size = -0.81, 95% CI [-1.19, -0.42], p = 0.03), diastolic blood pressure (pooled effect size = -0.63, 95% CI [-1.05, -0.21], p = 0.01), and BMD (pooled effect size = -0.40, 95% CI [-0.73, -0.07], p = 0.02) were significantly in favor of adrenalectomy group rather than conservative treatment but no significant differences between the two treatment groups in other MACS-related comorbidities were reported.Despite the limited and diverse data, this study demonstrates the advantage of adrenalectomy over conservative treatment for MACS-related comorbidities.